Spatio-Statistical Analysis of Temperature and Trend Detection in Baluchistan, Pakistan - Rafiq, Muhammad; Li, Yue Cong; Cheng, Yanpei; Rahman, Ghani; Ali, Ahmad; Iqbal, Muhammad; Latif , Ammara; Ali, Imtiaz; Rehan, Aqsa; Zahoor, Aun; et al. (Ecological Questions, 2022)
The assessment of temperature variability in any region of the world is important for prior planning in the context of current climate change. The mean monthly, seasonal and annual temperature data of nine meteorological stations was analysed in this study to determine the temperature variability and trend in Baluchistan province, Pakistan. The non-parametric Mann–Kendall and Sen’s slope estimator were applied to investigate the temperature trend pattern in the study Temperature data from the relevant meteorological stations (met-stations) were collected for this purpose from the Pakistan Meteorological Department and the National Center for Environmental Information. The result revealed an increasing significant trend (IST) in the mean annual temperature at Dalbandin, Kalat, Quetta, Zhob and Gawadar meteorological stations. While the seasonal minimum, maximum and mean temperature showed trend fluctuations in winter, spring and autumn seasons. In the seasonal analysis, the increasing trend has been detected in most of the meteorological stations (Dalbandin, Kalat, Quetta, Zhob, Khuzdar, Lasbella, Gawadar) in all four seasons. Whereas in Sibi met-station, a decreasing significant trend (DST) was recorded in summer (minimum, maximum and mean) and the met-station Barkhan recorded decreasing trend in maximum temperature in the autumn season. The Baluchistan province is totally spread over an arid and semiarid area of Pakistan where temperature fluctuations further aggravate the deprived agriculture and sparse natural vegetation.